Strategi Digital Marketing dan Word of Mouth Terhadap Keputusan Pemakaian Jasa Sand Blasting dan Vapor Blasting serta Powder Coating di BA BLAST Sidoarjo - Arianti, Andita Dwi; Nurhidayah, Nurhidayah; Hardaningtyas, Ratna Tri (UNIVERSITAS ISLAM MALANG, 2025)
Abstract In the era of Industry 4.0, consumerist lifestyles have become increasingly prevalent, particularly in the automotive sector, which has become a popular hobby among various groups. One common activity is the modification and restoration of vehicle components, leading to a growing demand for services such as sand blasting, vapor blasting, and powder coating. This study aims to analyze the influence of digital marketing strategies and Word of Mouth on consumer decisions to use these services at BA BLAST in Sidoarjo. A quantitative approach was employed through surveys distributed to customers who have used BA BLAST services. The results indicate that both digital marketing and Word of Mouth have a positive and significant impact on service usage decisions. Digital marketing enables effective and efficient promotion through social media, while Word of Mouth exerts a strong influence through recommendations from close contacts. This research is expected to serve as a reference for automotive service providers in formulating appropriate marketing strategies. Keywords: Digital Marketing, Word of Mouth, Consumer Decision, Automotive Services